Effect of calorific value on the burning rate of coconut shell briquettes and teak wood powder - Nur Aisah Sagala; Ety Jumiati; Ridwan Yusuf Lubis (Universitas Riau, 2024)
Biomass energy can be utilized inside, particularly in coconut shells with pine gum and teak sawdust as an elective fuel that is harmless to the ecosystem. To deliver charcoal briquettes from teak wood sawdust and coconut shells, this study endeavored to decide the qualities, impacts, and structure of varieties in pine tar cement. Pine resin adhesive is mixed with teak sawdust and coconut shells in a ratio of 80% to 20%, with variations of 30%, 40%, and 50%. For briquettes, utilize a size of 5 × 5 × 5 cm3. The aftereffects of the briquette test which delivered ideal qualities were gotten in example C with a warming worth of 31.073l J/gram and a consuming pace of 1,3697 g/minute according to SNI-01-6235-2000 and close to standard.